Electronic Government Meets Quality Management. A Study of Citizen Charters for Electronic Public Services in Spain. - Criado Grande, Juan Ignacio (Estado, Gobierno y Gestión Pública, 2007)
This paper focuses on the experience of Citizen Charters for Electronic Public Services (CCEPS) in the Spanish central level of government. It provides (1) evidences about an ongoing public sector management reform instrument addressing administrative transparency and orientation to the citizens in Spain. (2) Besides, the author points out the potential convergence between quality management and eGovernment, derived from this concrete case, but also previous experiences and trajectories of both type of modernization strategies, specially, in bureaucratic public administrations. This article presents a case study methodology, using a comparative approach addressing the study of past experiences and trajectories with quality management and eGovernment strategies. This paper provides fresh ideas about the necessity to adopt hybrid public sector management reform strategies, to transform government addressing the importance of electronic public services and the quality standards required to meet citizens requirements and expectations in eGovernment scenarios.